MANGROVE PLANTING AS AN EFFORT TO MITIGATE CLIMATE CHANGE ON SMALL ISLANDS - Sitanala, Merlin Renny; Siahaya, Ludia; Boreel, Aryanto; Talaohu, Moda (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Mangrove ecosystems have an important role in supporting the life of living things. The physical benefits of mangrove ecosystems are that they resist sea abrasion, withstand salt-laden storms and winds, and bind pollutant substances (poisons) in coastal waters. Climate change that occurs causes many problems, including extreme seasonal changes that cause abrasion, and rising sea levels due to melting polar ice. The problems that occur do not only affect the big islands but are also very much felt in the archipelago, especially Maluku which has many small islands. Efforts to conserve mangrove ecosystems are needed to minimize the impact caused by the effects of global warming. Conservation of mangrove ecosystems can reduce 10 to 31% of the estimated annual carbon emissions from the land use sector in Indonesia. This community service activity aims to realize climate change mitigation efforts on small islands, specifically in Negeri Suli, Maluku Province. Climate change mitigation efforts in Suli State, Maluku Province are carried out by providing socialization related to the role of mangrove ecosystems and then planting mangroves by existing youth and youth. in the village. Monitoring efforts are carried out by forming groups to monitor the success of mangrove growth. Replanting is carried out if mangrove seedlings are damaged or carried away by the current.